Cardiac magnetic resonance strain and mechanical dispersion assessment in patients with chronic total coronary artery occlusion. (14th October 2021) - Grafton-Clarke, C; Bhandari, S; Abdelaty, A; Mashicharan, M; Gulsin, G; Budgeon, C A; Hetherington, S; Kanagala, P; Ladwiniec, A; McCann, G P; Arnold, J R
Abstract: Background: Chronic total occlusions (CTO) are a frequent angiographic finding. Viability of CTO-subtended myocardium is dependent on the presence of an adequate collateral circulation. At rest, collateral supply may be sufficient to avert ischaemia and maintain normal systolic function. However, it remains unclear whether CTO-subtended myocardium may be considered truly normal, or whether subtle functional abnormalities may be present at rest. Purpose: To determine whether, in the absence of infarction and hibernation, CTO-subtended myocardium remains functionally normal or whether abnormalities of strain and/or mechanical dispersion may be present at rest. Methods: In a retrospective, single centre, observational study, we studied patients with ≥1 angiographically-diagnosed CTO referred for clinical stress perfusion cardiovascular magnetic resonance (CMR), and compared healthy volunteers (HVs) with a normal stress CMR scan. CMR imaging comprised functional and scar assessment with qualitative [visual] evaluation of infarction and segmental wall motion. Patients with infarction and/or wall motion score index (WMSI) ≥1 were excluded from further analysis. In remaining CTO subjects and HVs, segmental peak systolic longitudinal strain and circumferential strain were analysed (in 3 long-axis planes and 3 short-axis planes, respectively) and mechanical dispersion for both orientations was computed. Image analysis was performed using Medis (QStrain) software blinded to all clinical information. Results: From a total of 389 patients with ≥1 angiographically-diagnosed CTO, 68 had normal WMSI and no infarction (63.0±11.7 years, 79.4% male, LVEF 62.6±4.5%). Fifty HVs (61.1±7.0 years, 74.0% males, LVEF 61.1±5.3%) were also studied. The majority of CTO patients had concomitant coronary artery disease in at least one non-CTO vessel (n=37, 54.4%). GLS was lower in CTO patients than HVs (−21.8%±1.5% versus −24.0±1.1%; p<0.0001; Figure 1). By contrast, GCS was greater in CTO patients (−32.7±2.5% versus −28.8±2.1%; p<0.0001). Mechanical dispersion was increased in CTO patients (Figure 2), both longitudinally (90.3±14.6 ms in CTO patients versus 68.6±11.1 ms in HVs; p<0.0001) and circumferentially (66.7±9.1 ms versus 55.3±6.6 ms, respectively; p=0.02). Conclusion: Subclinical changes in left ventricular dynamics are present at rest in CTO patients with fully viable myocardium and no evidence of resting regional wall abnormality. Further study is warranted to evaluate the potential association between mechanical dispersion and arrhythmic events in CTO. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): NIHR Clinician Scientist Award (CS-2018-18-ST2-007 to J.R.A.) and Research Professorship award (RP-2017-08-ST2-007 to G.P.M.).